Spatial Layout Mechanism in Achieving Maximum Communication - Edison Hotaguan Manurung; Sri Prasetya Widodo; Flourentina; Longgam Saragi; Amrini Nofita Sibarani; Fitri Lestari; Imakulata Murni; Yogi Panjaitan; Irnandia Martilana Rizki; Nyoto Prasetyo (Indonesian Journal of Advanced Social Works, 2023)
The success of a campus organization in achieving goals efficiently depends on various factors, for example the knowledge and skills possessed by teachers will have a lot of influence in achieving the goals that have been set. Because an organization is basically a structured relationship system that coordinates the efforts of a group of people to achieve certain goals (Muhammad, 2002:24). Along with the development of human civilization, the campus has reached a very central position in human education, the campus no longer functions as a complement to family education but the campus as a source of inspiration in all aspects of human life. Spatial planning is one of the factors that can affect work effectiveness, with an organized and not boring campus layout that will be able to help the process of carrying out tasks properly planned by semester 7 students of the Faculty of Communication and Engineering, University of MPU tantular in recording activities or activities, processing, communication.